2014
DOI: 10.1051/0004-6361/201423441
|View full text |Cite
|
Sign up to set email alerts
|

New hydrogen-deficient (pre-) white dwarfs in the Sloan Digital Sky Survey Data Release 10

Abstract: We have detected 21 new, very hot hydrogen-deficient (pre-) white dwarfs (spectral types O(He), hot DO, PG1159) in the Data Release 10 of the Sloan Digital Sky Survey. We present the results of non-local thermodynamic equilibrium (non-LTE) model-atmosphere analyses. The seven PG1159 stars have effective temperatures and surface gravities in the ranges T eff = 100 000-140 000 K and log g = 6-7.5. The hottest one is a new member of the rare hybrid-PG1159 subtype, indicating the presence of residual hydrogen. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 16 publications
6
42
1
1
Order By: Relevance
“…Interestingly, we find that other He-dominated objects (e.g. He-rich subdwarfs; Müller-Ringat 2013; Németh et al 2012;Naslim et al 2010;Hirsch 2009;Ahmad et al 2004;Rauch et al 1998Rauch et al , 1991Husfeld et al 1989;Stroeer et al 2007, DO WDs Werner et al 2014;Mahsereci 2011;Hügelmeyer et al 2006;Dreizler & Werner 1996) also show these differences in the CNO abundances 13 . Some objects are enriched in N but not in C, some C-enriched objects do not show N, but there also are objects which are enriched in both.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…Interestingly, we find that other He-dominated objects (e.g. He-rich subdwarfs; Müller-Ringat 2013; Németh et al 2012;Naslim et al 2010;Hirsch 2009;Ahmad et al 2004;Rauch et al 1998Rauch et al , 1991Husfeld et al 1989;Stroeer et al 2007, DO WDs Werner et al 2014;Mahsereci 2011;Hügelmeyer et al 2006;Dreizler & Werner 1996) also show these differences in the CNO abundances 13 . Some objects are enriched in N but not in C, some C-enriched objects do not show N, but there also are objects which are enriched in both.…”
Section: Resultsmentioning
confidence: 48%
“…Rauch et al (2008) suggested that RCB stars might be possible progenitors of the O(He) stars. This could be true for the two C and N enriched O(He) stars SDSS J 172854.34+361958.62 (Werner et al 2014) and KPD 0005+5106 (Wassermann et al 2010). In between evolutionary objects could be the C-and N-enriched luminous sdO stars LSE 259 (Husfeld et al 1989), GJJC 1 (Rauch et al 1998), and KS 292 (Rauch et al 1991).…”
Section: Single-star Evolutionmentioning
confidence: 97%
See 1 more Smart Citation
“…The element abundances are summarized in Table 4 and displayed in Fig. 7, together with results for RCB and EHe stars (from Jeffery et al 2011, and references Currently, ten objects were assigned to the group of O(He) stars (Reindl et al 2014;Werner et al 2014;De Marco et al 2015). They cover a parameter range of T eff = 80 000−195 000 K and log g = 5.0−6.7.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For the spectral analysis we used our non-LTE code TMAP 8 (Werner et al 2012) to compute plane-parallel, line-blanketed atmosphere models in radiative and hydrostatic equilibrium (Werner & Dreizler 1999;Werner et al 2003). They include the three most abundant elements in H1504+65, namely, C, O, and Ne.…”
Section: Model Atoms and Model Atmospheresmentioning
confidence: 99%